192 Terpenes as antinutritive chemicals in red cedar. (29th July 2019) - Lourencon, Raquel; Hart, Steven P; Gipson, Terry A; Adams, Bob; Rassi, Davila
Abstract: At some research sites goats aggressively consumed red cedar (Juniperus virginiana) throughout the year, while at other sites goats consumed little cedar, although they consumed more cedar in winter. It was hypothesized that differences in red cedar intake may be caused by terpenes. The purpose of this study was to measure terpenes in cedar needles at different locations and times of the year. Ninety-one samples of red cedar needles were obtained from four locations (Langston, OK; Midwest City, OK; Mannford, OK; Neosho, MO) at monthly intervals over a 2-yr period. Needles were manually stripped from branches at approximately 1.5 m high from at least 25 plants at each location. Sixty grams of cedar needles were extracted by steam distillation for 2 h. Some samples were exhaustively extracted for a further 6 h to calculate recovery (45.7%). Two mL of diethyl ether were added, containing 1 mg/mL of methyl decanoate (internal standard), samples were vortexed and the ether was dried with a stream of nitrogen. Samples were subjected to gas chromatography for terpenes. The total amount of terpenes (mg/g DM) was calculated as the sum of peak areas/peak area of the internal standard x 2 mg internal standard/ 0.457/ dried weight of cedar needles. Months were categorized as season. Data were analyzed using the SAS GLM procedure with factors of season, year, and location. Neither season (P > 0.8) nor location (P > 0.25) nor the interaction (P > .9) were significant factors determining total terpene content of red cedar. Concentration of total terpenes for Langston was 20.8, Mannford 18.4, Neosho 15.2, and OKC 18.6 mg/g DM. Concentration by season was Fall 17.1, Spring 18.6, Summer 17.5, and Winter 19.7 mg/g DM. Total terpene concentration does not seem to be a factor affecting red cedar consumption by goats.